2010
DOI: 10.1002/cncy.20126
|View full text |Cite
|
Sign up to set email alerts
|

Anal cancer and cervical cancer screening: Key differences

Abstract: Cervical cancer and anal cancer share many similarities including causation by oncogenic human papillomaviruses; however, significant differences exist in their epidemiology, risk factors, biologic behavior, management, and treatment. Although rare, the incidence of anal cancer is alarmingly high and continues to increase in high-risk populations, particularly men who have sex with men regardless of their human immunodeficiency virus (HIV) status. There are no national screening guidelines for anal cancer. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
213
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(228 citation statements)
references
References 66 publications
5
213
0
10
Order By: Relevance
“…However, anal cytology has been shown to have a much lower sensitivity for HGSIL (46%) than for LGSIL (77%) or ASCUS (87%) in an HIV-positive population. 7 It is possible that high-grade disease was present and went undetected due to the relatively low sensitivity of this screening tool. Some authors have reported higher percentages of HGSIL in their HIV-positive populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, anal cytology has been shown to have a much lower sensitivity for HGSIL (46%) than for LGSIL (77%) or ASCUS (87%) in an HIV-positive population. 7 It is possible that high-grade disease was present and went undetected due to the relatively low sensitivity of this screening tool. Some authors have reported higher percentages of HGSIL in their HIV-positive populations.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of HPV infection and anal cancer in HIV-infected individuals and men who have sex with men (MSM) have led to a growing concern that screening, prevention and early intervention efforts need to be implemented, similar to other cancers 4 . Baseline and annual follow up anal cytological screening is recommended for HIV-infected individuals in the New York State Guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Progression and regression rates from HPV infection to anal cancer are unknown, but the screening process is similar to the highly effective cervical cancer model 4 . While there is no universally accepted anal cancer screening or treatment protocol, typically, the screening process involves two stages.…”
Section: Introductionmentioning
confidence: 99%
“…However, high-resolution anoscopy provides additional evaluation even for patients with negative Pap smears [22,23].…”
Section: Discussionmentioning
confidence: 99%